ChemInform Abstract: Irigermanone, a Noriridal with Unprecedented Methylketone Function, from Iris germanica. Issue 19 (13th May 2014) - Potterat, Olivier; Herzog, Carmela; Raith, Melanie; Ebrahimi, Samad Nejad; Hamburger, Matthias
Abstract isolation and structure determination of irigermanone (I) along with nine known congeners